اجتماعی اجتہاد بذریعہ مجلس اہل حل وعقد: تصور اور تاریخ: Collective Ijtihād Through Majlis Ahl Ḥall wa ʿAqd: Concepts and History - Dr. Muhammad Zubair; Dr. Hafiz Muhammad Tahir Islam (MEI, 2023)
There are two types of Ijtihād: individual and collective. When an individual Muslim Jurist perform Ijtihād it is called individual Ijtihād and when a Council of Islamic Jurists or qualified scholars undertake utmost effort to discover the Sharia ruling then it is called collective Ijtihād. This research article identifies different ways of collective Ijtihād. A governmental and non-governmental organization of qualified scholars i.e. Majlis Ahl Ḥall wa ʿAqd is also an appropriate platform for collective Ijtihād. Such jurists’ groups must be established in every Islamic country and society. In addition, there should be an international jurist’s counseling organization, which represents the entire Muslim Ummah.